Conceptual Framework of Civic Competence - Jurs, Pāvels (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
There is a crucial importance for the country in the diverse participation of. Being aware of the potential of interaction of individual, community and the society, thus with a help of civic education facilitating the development of individual's civic competence. However, for basing the pedagogical activities of the formation of citizenship on the primary stage, it is necessary to develop a model of civic competence. Summarizing and analysing a number of theoretical approaches, using theoretical methods of research and being aware of the curriculum regulatory framework in the publication, developed model of civic competences is provided for the further discussion. Thus, through civic education and assuming the developed model of civic competences, young people's civic knowledge, responsibility, civic skills and capacity to participate in decision-making processes can be contributed.